2021
DOI: 10.3390/life11060466
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Effects of PCSK9 Inhibitors in Primary Hypercholesterolemia

Abstract: Proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors are a novel group of hypolipidemic drugs that are recommended particularly for high-risk hypercholesterolemia patients, including those with primary hypercholesterolemia (PH), where lifelong exposure to high low-density lipoprotein (LDL) cholesterol levels results in an elevated risk of atherosclerosis at an early age. The onset and progression of atherosclerosis is significantly influenced by activated platelets. Oxidized LDL influences platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 124 publications
(159 reference statements)
0
15
0
Order By: Relevance
“…As a result, in presence of PSCK9 antibodies, platelet-dependent thrombus formations significantly reduced [68]. Many studies indicate that statins [69] and PCSK9 monoclonal antibodies [70] have an effect on the hemostatic system. In approximately a third of patients, platelets show suboptimal response to antithrombotic therapy that can be linked to hypercholesterolemia [71].…”
Section: Pcsk9 and Platelets' Functionmentioning
confidence: 99%
“…As a result, in presence of PSCK9 antibodies, platelet-dependent thrombus formations significantly reduced [68]. Many studies indicate that statins [69] and PCSK9 monoclonal antibodies [70] have an effect on the hemostatic system. In approximately a third of patients, platelets show suboptimal response to antithrombotic therapy that can be linked to hypercholesterolemia [71].…”
Section: Pcsk9 and Platelets' Functionmentioning
confidence: 99%
“…Furthermore, recent studies suggested a novel role for PCSK9 in promoting atherosclerosis through platelet activation, a key role during atherogenesis and in atherothrombosis-induced MI [35,36,[62][63][64]. Notably, several clinical studies have demonstrated the antiplatelet effects of PCSK9 in patients with hypercholesterolemia and found it to be an effective and safe strategy for treating patients with uncontrolled hyperlipidemia and coronary artery disease [65,66].…”
Section: Pcsk9 and MImentioning
confidence: 99%
“…CD46 and LOX-1 are involved in them [ 69 , 70 ] and, accompanied by ox-LDL binding protein, play a key role in the formation of blood clots [ 71 ]. A separate mechanism is associated with the toll-like receptor 2 (TLR-2) stimulation, which activates the process of platelet aggregation through lipid-peroxide-modified phospholipids in the transport of Lp(a) [ 72 , 73 , 74 ].…”
Section: Pcsk9 and Atherosclerosismentioning
confidence: 99%